Data for: "Estimating surface concentrations of Calanus finmarchicus using standardised eRGB imagery" ... - McCarry, Cait (University of Strathclyde, 2023)
This dataset contains figures, MATLAB scripts and data required to apply the novel techniques developed in the paper. The 'ReadMe' file contrains more information about each of the files in the folder. ...